Perceptions of Students, Faculty and Administrative Staff on the Data Privacy Act: An Exploratory Study - Ramos, David Paul (JPAIR Multidisciplinary Research, 2019)
The Data Privacy Act of 2012 was enacted to “protect the fundamental human right of privacy of communication while ensuring a free flow of information to promote innovation and growth.” Data privacy pertains to the right of an individual not to disclose his or her information. Since privacy is a universal human right, it is the responsibility of the government to protect the rights of its people to privacy and provide measures to protect their data. Given that the Data Privacy Act’s implementation is a relatively recent development in the Philippines, little is known about the various stakeholders’ perceptions towards it. A qualitative study that utilized semi-structured interviews were conducted to explore selected students’, faculty member’s, and administrative staffs’ perceptions of the Data Privacy Act. Non-probability, purposive sampling was used to recruit six respondents. An interview guide was developed to help in the facilitation of the interviews. Data were analyzed through the 6-step thematic analysis by Braun & Clarke (2006). Four themes emerged: 1) Limited awareness of the law, 2) Somewhat familiar with the purpose/ functions of the law, 3) Issues in the implementation of the law in the academe, and 4) Ambiguity in the necessity of the law. Recommendations to improve compliance with the Data Privacy Act, such as the designation of personal information controllers or data privacy officers (DPO) to ensure that security measures are in place to protect personal and sensitive information, were also discussed.